Novel 9 amino acid in‐frame deletion in the NTRK1 tyrosine kinase domain in a patient with congenital insensitivity to pain with anhydrosis. Issue 5 (21st September 2017) - Amin, S.; Forrester, N.; Norman, A.; Lux, A.; Vijayakumar, K.
Abstract : Schematic presentation of NTRK1 protein structure. Variants identified in this study are shown in red and previously reported variants associated with CIPA are shown in black (LRM, leucine rich motif; Ig, immunoglobulin‐like domain; TM, transmembrane domain; TK, tyrosine kinase domain).